2019
DOI: 10.21082/jhort.v29n1.2019.p69-80
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Konsentrasi Lethal dan Waktu Lethal Insektisida Botani Terhadap Ulat Bawang (Spodoptera exigua) di Laboratorium

Abstract: <p><strong>[Evaluation of Lethal Concentration and Lethal Time of Botanical Insecticide Against Beet Armyworm (<em>Spodoptera exigua</em>) in The Laboratory]</strong></p><p>Pemanfaatan insektisida botani merupakan salah satu pilihan untuk mengendalikan serangan hama Spodoptera exigua yang ramah lingkungan. Tujuan penelitian adalah untuk menetapkan konsentrasi sublethal dan waktu prolethal insektisida botani terhadap larva instar ketiga S. exigua di laboratorium. Percob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…According to Maini and Rejesus [24], leaf extract of derris contains active compounds, such as dequelin (0.15 -2.9%), eliptone (0.35 -4.6%) and toxicarol (0 -4.4%). While Hasyim et al [21] found that from the results of GC-MS analysis, leaf extract of derris contained 7-isopropensil-1, 4a dimethyl-4, 4a, 5,5,7,8hexahydro-3 H-naphthalen-2-0 ne, squalen2 , ergosi-5-en-3-ol, compesterol stigmasterol, rotenone, gamma-sitosterol, 2,3,6-trimethoxy-5-methylphenol, and n-hexadeconoic acid. Based on these contents, it is possible that there are active ingredients that greatly affect the suppression of C. capsici pathogens.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Maini and Rejesus [24], leaf extract of derris contains active compounds, such as dequelin (0.15 -2.9%), eliptone (0.35 -4.6%) and toxicarol (0 -4.4%). While Hasyim et al [21] found that from the results of GC-MS analysis, leaf extract of derris contained 7-isopropensil-1, 4a dimethyl-4, 4a, 5,5,7,8hexahydro-3 H-naphthalen-2-0 ne, squalen2 , ergosi-5-en-3-ol, compesterol stigmasterol, rotenone, gamma-sitosterol, 2,3,6-trimethoxy-5-methylphenol, and n-hexadeconoic acid. Based on these contents, it is possible that there are active ingredients that greatly affect the suppression of C. capsici pathogens.…”
Section: Resultsmentioning
confidence: 98%
“…The use of leaf extract of derris for pest control has been widely practiced. Hasyim et al [21] has evaluated of leaf extract of derris on concentration and lethal time in onion caterpillar (Spodoptera exigua) in the laboratory. Meanwhile, leaf extract of derris for disease control have been tried against Fusarium oxysporum [22].…”
Section: Introductionmentioning
confidence: 99%
“…Enzim protease akan menurun akibat adanya aktivitas saponin serta dapat mengganggu penyerapan makanan (Chaieb, 2010;Kuddus et al, 2011). Masuknya saponinke dalam tubuh larva mengakibatkan terganggunya sekresi enzim pencernaan, dengan tidak adanya enzim pencernaan maka metabolisme pencernaan akan terganggu, sehingga akan mengakibatkan larva mati karena kekurangan nutrisi untuk kelangsungan hidupnya (Hasyim et al, 2019). Mekanismekerja dari senyawa saponin ialah sebagai stomach poisoning pada ulat dengan cara saponin akan menurunkan tegangan permukaan selaput mukosa traktus digertivus ulat sehingga dinding traktus digestivus menjadi korosif.Saponin juga menyebabkan iritasi lambung apabila dimakan (Utami, 2010).Adanya senyawa saponin diduga juga menyebabkan ulat grayak mengalami gagal melakukan pergantian kulit (molting) (Gambar c).…”
Section: Hasil Dan Pembahasanunclassified
“…Phytochemical test results showed that essential oils contain secondary metabolites in the form of alkaloids, terpenoids, and tannins (4). Toxic alkaloids and nerve poisons are alkalic substances and contain one or more nitrogen atoms (24). The research results conducted by Samilati, et al (4) showed that the death of mosquito larvae given Allium sativum solution was through four phases, namely stimulation (changes in larval behavior from normal circumstances), convulsions, paralysis, and ended with death.…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
“…Tannins found in Citrus limon and Allium sativum are toxic, have a bitter taste, and have an antifeedant effect (23). Tannins play a role in disrupting the process of absorption of proteins needed for growth by binding to proteins in the digestive system of insects (24).…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%